ASSOCIATION BETWEEN SUBJECTIVELY EVALUATED COGNITION AND PERFORMANCE IN COMPUTERIZED COGNITION TESTING AMONG AGING WORKERS - Noutia, Jemina (My University, 2021)
Cognition can be measured with objective tests, but also subjective evaluation is used. This study aimed to examine how subjectively evaluated cognition is comparable to objective test results observed in computerized test pattern. Such association would be significant for quick and reliable cognitive screening in clinical use. The study population consisted of 283 participants (mean age 62,4 years, SD 1,0, 82% females) from the Finnish Retirement and Aging Study. Self-evaluation of cognition was conducted by questions concerning memory, learning and concentration and objective evaluation with a computerized assessment of cognition; Cambridge Neuropsychological Test Automated Battery (CANTAB). Five CANTAB sub-tests assessing memory, executive function, attention and information processing, were included. Sleep difficulties were measured with Jenkins Sleep Problem Scale and depressive symptoms with Beck Depression Inventory, and they were controlled for the analysis. Analysis of variance was used to compare subjective and objective results. In subjective evaluation, very good and good answers formed a majority. Memory was evaluated as moderate by 18 % and poor by 2 % of the participants, concentration moderate by 21 % and poor by 3% and learning skills moderate by 32 % and poor by 4 % of the participants. In the analysis, poor self-perceived memory was associated with poorer performance on spatial working memory test. No statistically significant association was found between self-perceived learning or concentration and the cognitive tests. In conclusion, on aging workers subjective memory concerns were weakly linked to poorer performance in computerized test, that focus on executive function and working memory.
Keywords: aging worker, cognition, memory, concentration, learning